Changing scenario during COVID-19 pandemic - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2020)
Regular activities, management, behavior, livelihood and regulations have been altered and customized during pandemic to cope with the newly appeared challenges. All steps of life have been affected unexpectedly. The epidemiological, political, clinical and psychosocial scenarios have been changing as the time passes; thus the initial guidelines and regulation are not enough to combat crisis over time.Keywords: covid, crisis, guideline, pandemic, testing